Conditional N-WASP knockout in mouse brain implicates actin cytoskeleton regulation in hydrocephalus pathology - Jain, Neeraj (2015)
Cerebrospinal fluid (CSF) is produced by the choroid plexus and moved by multi-ciliated ependymal cells through the ventricular system of the vertebrate brain. Defects in the ependymal layer functionality are a common cause of hydrocephalus. N-WASP (Neural-Wiskott Aldrich Syndrome Protein) is a brain-enriched regulator of actin cytoskeleton and N-WASP knockout caused embryonic lethality in mice with neural tube and cardiac abnormalities. To shed light on the role of N-WASP in mouse brain development, we generated N-WASP conditional knockout mouse model N-WASPfl/fl; Nestin-Cre (NKO-Nes). NKO-Nes mice were born with Mendelian ratios but exhibited reduced growth characteristics compared to their littermates containing functional N-WASP alleles. Importantly, all NKO-Nes mice developed cranial deformities due to excessive CSF accumulation and did not survive past weaning. Coronal brain sections of these animals revealed dilated lateral ventricles, defects in ciliogenesis, loss of ependymal layer integrity, reduced thickness of cerebral cortex and aqueductal stenosis. Immunostaining for N-cadherin suggests that ependymal integrity in NKO-Nes mice is lost as compared to normal morphology in the wild-type controls. Moreover, scanning electron microscopy and immunofluorescence analyses of coronal brain sections with anti-acetylated tubulin antibodies revealed the absence of cilia in ventricular walls of NKO-Nes mice indicative of ciliogenesis defects. N-WASP deficiency does not lead to altered expression of N-WASP regulatory proteins, Fyn and Cdc42, which have been previously implicated in hydrocephalus pathology. Taken together, our results suggest that N-WASP plays a critical role in normal brain development and implicate actin cytoskeleton regulation as a vulnerable axis frequently deregulated in hydrocephalus.